Anthrax: has the clinical milieu changed since 2001? - Amesh A. Adalja (Greater Baltimore Medical Center, 2012)
Since the anthrax attacks of 2001 (Amerithrax), several important improvements in the knowledge of Bacillus anthracis and the clinical condition it causes have occurred. While much remains to be known about the optimal management of anthrax patients, several approaches that were not widely utilized, available, or known in 2001 would be used in the treatment of critically ill anthrax patients in 2012.